Andrew Lang’s “Literary Plagiarism”: Reading Material and the Material of Literature - Henville, Letitia (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
This paper examines the metaphors used in Andrew Lang’s 1887 Longman’s Magazine article “Literary Plagiarism,” arguing that Lang repeatedly describes ideas as if they are objects in order to frame the late-nineteenth-century plagiarism debate as a discussion of the best use of materials. Lang’s slippage between abstract, intangible ideas and “the material of literature” (833) enabled him to circumvent a discussion about access to publishing networks. This paper suggests that this episode exposes a concrete historical backstory for recent developments in thing theory, and suggests that the latter recapitulates in a philosophical register debates about the economics of literary publishing taking place in the late nineteenth century.